Advancing agricultural trade reforms: Latin American contributions to the multilateral trading system - Abraham Peralta, Gloria (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
It discusses the region's progress in agricultural trade reforms and its contributions to the multilateral trade system. It includes information about the region's agricultural proposals on seven negotiation topics: internal support, market access, export competition, export restrictions, cotton, special safeguard mechanism, and public stockholding for food security. Additionally, it highlights Costa Rica's proposal to reduce levels of trade-distorting support and establish a cap on existing support levels. Finally, It identifies the agricultural trade challenges the region is facing and examines the strategies being implemented to address them